Immunogenicity induced by two and three doses of the BNT162b2 mRNA vaccine in patients with autoimmune inflammatory rheumatic diseases and immunocompetent controls: a longitudinal multicentre study. Issue 11 (22nd July 2022) - Furer, Victoria; Eviatar, Tali; Freund, Tal; Peleg, Hagit; Paran, Daphna; Levartovsky, David; Kaufman, Ilana; Broyde, Adi; Elalouf, Ofir; Polachek, Ari; Feld, Joy; Haddad, Amir; et al.
Abstract : Objectives: To evaluate long-term kinetics of the BNT162b2 mRNA vaccine-induced immune response in adult patients with autoimmune inflammatory rheumatic diseases (AIIRD) and immunocompetent controls. Methods: A prospective multicentre study investigated serum anti-SARS-CoV-2 S1/S2 IgG titre at 2–6 weeks (AIIRD n=720, controls n=122) and 6 months (AIIRD n=628, controls n=116) after the second vaccine, and 2–6 weeks after the third vaccine dose (AIIRD n=169, controls n=45). T-cell immune response to the third vaccine was evaluated in a small sample. Results: The two-dose vaccine regimen induced a higher humoral response in controls compared with patients, postvaccination seropositivity rates of 100% versus 84.72%, p<0.0001, and 96.55% versus 74.26%, p<0.0001 at 2–6 weeks and at 6 months, respectively. The third vaccine dose restored the seropositive response in all controls and 80.47% of patients with AIIRD, p=0.0028. All patients treated with methotrexate monotherapy, anticytokine biologics, abatacept and janus kinase (JAK) inhibitors regained the humoral response after the third vaccine, compared with only a third of patients treated with rituximab, entailing a 16.1-fold risk for a negative humoral response, p≤0.0001. Cellular immune response in rituximab-treated patients was preserved before and after the third vaccine and was similar to controls. Breakthrough COVID-19 rate during the Delta surge was similar in patients and controls, 1.83% versus 1.43%, p=1. Conclusions: The two-dose BNTb262 regimen was associated with similar clinical efficacy and similar waning of the humoral response over 6 months among patients with AIIRD and controls. The third vaccine dose restored the humoral response in all of the controls and the majority of patients.